2022
DOI: 10.1002/exp.20210145
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic covalent polymeric antimicrobial for conquering drug‐resistant bacterial infection

Abstract: Increasing bacterial drug resistance to antibiotics has posed a major threat to contemporary public health, which resulted in a large number of people suffering from serious infections and ending up dying without any effective therapies every year. Here, a dynamic covalent polymeric antimicrobial, based on phenylboronic acid (PBA)installed micellar nanocarriers incorporating clinical vancomycin and curcumin, is developed to overcome drug-resistant bacterial infections. The formation of this antimicrobial is fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…2 It is worrying that the emergence of multidrug-resistant (MDR) Gram-negative bacteria 3 in ESKAPE 4 has posed serious health impacts to human beings. 5 Recently, the World Health Organization (WHO) reported that the rate of resistance to ciprofloxacin (Cip) varied from 8.4% to 92.9% for Escherichia coli and from 4.1% to 79.4% for Klebsiella pneumoniae. 6 It is estimated by WHO that the improper use of antibiotics during the COVID-19 pandemic will further exacerbate this trend, and hence overcoming the drug resistance of Gram-negative bacteria can become a major global security challenge in the near future.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 It is worrying that the emergence of multidrug-resistant (MDR) Gram-negative bacteria 3 in ESKAPE 4 has posed serious health impacts to human beings. 5 Recently, the World Health Organization (WHO) reported that the rate of resistance to ciprofloxacin (Cip) varied from 8.4% to 92.9% for Escherichia coli and from 4.1% to 79.4% for Klebsiella pneumoniae. 6 It is estimated by WHO that the improper use of antibiotics during the COVID-19 pandemic will further exacerbate this trend, and hence overcoming the drug resistance of Gram-negative bacteria can become a major global security challenge in the near future.…”
mentioning
confidence: 99%
“…Antimicrobial resistance (AMR) is an ever-increasing public threat to global health, and it has caused at least 700 000 deaths . It is worrying that the emergence of multidrug-resistant (MDR) Gram-negative bacteria in ESKAPE has posed serious health impacts to human beings . Recently, the World Health Organization (WHO) reported that the rate of resistance to ciprofloxacin (Cip) varied from 8.4% to 92.9% for Escherichia coli and from 4.1% to 79.4% for Klebsiella pneumoniae .…”
mentioning
confidence: 99%
“…Their similar release behaviors were mainly due to the p-p stacking interaction between Van and Cur. 52 This long-term, sustainable and stable multi-drug release is essential for the long-term inhibition of intracellular bacterial growth. 53,54 In addition, TEM images showed that (Van 1.5 + Cur 3.0 )@F(AM) NPs were homogeneous spherical particles with an average diameter of 357 nm (Fig.…”
Section: Extracellular Antibacterial Evaluation and Characterization ...mentioning
confidence: 99%
“…Cumulative evidence demonstrated that some aromatic photosensitizers [e.g., chlorophyll (Chl) and curcumin] are natural antibacterial compounds extracted from plants with low toxicity. They have been proved to possess broad bactericidal activity against not only Gram-positive but also Gram-negative bacteria via interacting with cellular components of bacteria. , Chl is a natural photosensitizer for PDT with the advantages of excellent ROS yield and good biocompatibility . To overcome the dilemmas include antibacterial adhesion and bactericidal strategies, both have limitations and most porphyrin-based photosensitizers have toxicity, thus a synergistic antibacterial surface consisting of both superhydrophobic and PDT characteristics would be an interesting strategy to inactivate bacteria without triggering drug resistance and effectively inhibit bacterial infection.…”
Section: Introductionmentioning
confidence: 99%